Proceedings of jAUTI24 : XIII Iberoamerican Conference on Applications and Usability of Interactive Digital TV - Abásolo Guerrero, María José (2025)
The XIII Ibero-American Conference on Applications and Usability of Interactive Digital Television (jAUTI 2024) was jointly organized by the University of Córdoba (Spain) and RedAUTI (Thematic Network on Applications and Usability of Interactive Digital Television). The event was held from November 13 to 15, 2024, in Santo Domingo, Dominican Republic. This publication compiles 19 research papers presented during the conference, addressing diverse topics such as infrastructure, design, development, and user experiences related to interactive digital television and associated information and communication technologies. A single blind peer-review process was carried out to produce the final versions included in this publication.